1995
DOI: 10.1016/0925-4439(94)00072-x
|View full text |Cite
|
Sign up to set email alerts
|

Copper incorporation into ceruloplasmin in rat livers

Abstract: Ceruloplasmin, a blue copper oxidase found in plasma, is synthesized in hepatocytes as a single polypeptide chain consisting of a 19 amino acid leader peptide plus 1046 amino acids of mature protein (132 kDa). Holoceruloplasmin is secreted into the plasma with 6-7 atoms of copper bound per molecule. In this study we identified apo- and holoceruloplasmin and examined the mechanism of copper incorporation during ceruloplasmin biosynthesis using the Long-Evans Cinnamon (LEC) rat which does not incorporate copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 22 publications
4
42
0
Order By: Relevance
“…The expression, localization, and function of ATP7B has been extensively studied and characterized using in vitro models to understand the role of ATP7B in the homeostatic control of Cu and its altered function in disease states. Under low Cu concentrations, ATP7B is localized to the TGN, where its primary function is to transport Cu across the Golgi membrane for incorporation into ceruloplasmin and excretion across the basolateral membrane into the blood (Murata et al, 1995;Terada et al, 1995;Hellman et al, 2002). Results obtained in this study showed that SCRH were able to synthesize and secrete ceruloplasmin in culture.…”
Section: Downloaded Fromsupporting
confidence: 48%
“…The expression, localization, and function of ATP7B has been extensively studied and characterized using in vitro models to understand the role of ATP7B in the homeostatic control of Cu and its altered function in disease states. Under low Cu concentrations, ATP7B is localized to the TGN, where its primary function is to transport Cu across the Golgi membrane for incorporation into ceruloplasmin and excretion across the basolateral membrane into the blood (Murata et al, 1995;Terada et al, 1995;Hellman et al, 2002). Results obtained in this study showed that SCRH were able to synthesize and secrete ceruloplasmin in culture.…”
Section: Downloaded Fromsupporting
confidence: 48%
“…A possible source of this additional copper is the Cu-protein ceruloplasmin, which is known to be synthesized in the mammary gland and excreted in the milk [18,25]. Normally, it is thought that ceruloplasmin would receive copper in the TGN from ATP7B [26]. However, in the tx mouse this cannot be the case as the mutant Atp7b is unable to transport copper [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its ATP-driven copper transport role at the TGN where copper is incorporated into ceruloplasmin (25,26), the Wilson disease protein is also thought to be involved in the excretion of copper into bile at the canalicular membrane (27). The copper-stimulated trafficking of the transporter between the TGN and the canalicular membrane may involve the N terminus and is not clearly understood (28).…”
Section: The Wilson Disease Coppertransporting P-type Atpasementioning
confidence: 99%